2014
DOI: 10.1159/000368089
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasonography for Tumor Node Staging and Vascular Invasion in Pancreatic Cancer: A Meta-Analysis

Abstract: Background/Aims: The accurate staging of pancreatic cancer (PanCa) is crucial in the development of a stage-specific treatment plan for PanCa patients. We aimed to perform a meta-analysis of endoscopic ultrasonography (EUS) in the tumor node (TN) staging and evaluation of vascular invasion in PanCa. Methods: A meta-analysis of diagnostic accuracy parameters was performed to evaluate the EUS-based TN staging, and vascular invasion by PanCa was compared to the results of intraoperative staging or to the histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…An analysis of 20 studies and 726 cases of pancreatic cancer showed that EUS for T1-T2 staging has a sensitivity and specificity of 0.72 and 0.90, respectively. 19 Sensitivity and specificity for T3-T4 staging is 0.90 and 0.72, respectively. The role of EUS in staging is felt to be complementary to pancreas protocol CT, which is considered the gold standard.…”
Section: Imaging Evaluationsmentioning
confidence: 95%
See 1 more Smart Citation
“…An analysis of 20 studies and 726 cases of pancreatic cancer showed that EUS for T1-T2 staging has a sensitivity and specificity of 0.72 and 0.90, respectively. 19 Sensitivity and specificity for T3-T4 staging is 0.90 and 0.72, respectively. The role of EUS in staging is felt to be complementary to pancreas protocol CT, which is considered the gold standard.…”
Section: Imaging Evaluationsmentioning
confidence: 95%
“…Criteria for Resection: The NCCN Panel recommends that pancreatic resections be performed at institutions that perform a large number (at least [15][16][17][18][19][20] of pancreatic resections annually. It is again emphasized that institutions performing pancreatic resections should have a multidisciplinary team with focus in pancreatic cancer that actively participates in the decision-making process regarding which patients should undergo surgery.…”
Section: -126mentioning
confidence: 99%
“…Although Kayahara and Sakai [56,82] were unable to find a significantly different survival rate for LN-positive patients with or without metastases to PALNs, several other authors confirmed a significantly worse prognosis for patients with metastatic PALNs [54,64,65], also in a multi-institutional series of 822 patients [83]. The preoperative diagnosis of metastatic PALNs can spare some patients surgery, but the accuracy of helical CT, MRI, EUS, and 18-FDG PET is unfortunately quite low [68][69][70][71][72][73][74][75][76][77][78]. The intraoperative diagnosis of metastatic disease on frozen section in PALNs enables a patient's risk/benefit to be reassessed before proceeding with such a complex and risky procedure as PD.…”
Section: Proposal For a Standard Lymphadenectomymentioning
confidence: 99%
“…For T3-4 tumors, EUS had 90% sensitivity and 72% specificity. 156 This modality can detect lesions as small as 2-3 mm in the pancreas, 157 which is generally the resolution of CT and MRI. Even though EUS has excellent performance with visualizing and diagnosing PDAC, it is mainly used as part of the workup to obtain fine-needle aspiration or biopsy material in patients suspected of having a primary tumor.…”
Section: Traditional Imaging Techniques For Pancreatic Cancer Detectionmentioning
confidence: 99%